Transformational Leadership of Pesantren as a Role Model for Contemporary Islamic Education Institutions - Basri, Hasan; Hasibuan, Hilman Rizky; Ab Rahman, Zaizul (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This study aims to find out about the transformational leadership of Islamic boarding schools as role models in contemporary Islamic educational institutions dan and knowing the characteristics of Islamic boarding school transformational leadership. This research method is library research. Library research is research in which the data or materials needed to complete research come from the library in books, encyclopedias, dictionaries, journals, magazines and so on. The results of this study indicate that the transformational leadership model of pesantren as a role model for contemporary Islamic educational institutions must have four dimensions: charismatic leadership, a leader who can make his followers admire, respect, and trust him. Inspirational motivation leadership, leaders who can articulate clear expectations from all members. Intellectual stimulation leadership is a leader who can develop new ideas from his subordinates. And individualized consideration leadership is a leader who always listens to the aspirations and inputs of others. This research provides practical implications and policy recommendations for Islamic boarding schools and other Islamic educational institutions that wish to adopt transformational leadership strategies. With a better understanding of the role of transformational leadership in Islamic boarding schools, it is hoped that Islamic boarding schools can continue to develop as models of contemporary Islamic education that are relevant and competitive in today's digital era